On the derivational interpretation of borrowed nouns with the suffix -acij-a - Inčiuraitė-Noreikienė, Lina; Stundžia, Bonifacas (Baltistica, 2024)
This article examines borrowed nouns with the suffix -acij-a in contemporary Lithuanian. A synchronic derivational-morphological analysis identifies two strata of borrowed nouns with this suffix: 1) correlative formations (ca. 84%) and 2) simplex words (ca. 16%), e.g., damnifikacija ‘damnification’. Correlative formations consist of 1a) suffixed derivatives (ca. 92%), derived from morphonologically adapted, derivationally unanalyzable borrowed verbs or, less commonly, nouns (ador-acij-a ‘adoration’ ⇠ ador-uo-ti ‘to adore’, sufiks-acij-a ‘suffixation’ ⇠ sufiks-as ‘suffix’) and morphonologically adapted, derivationally analyzable verbs or, rarely, nouns (vakcin-acij-a ‘vaccination’ ⇠ vakcin-uo-ti ‘to vaccinate’ ⇠ vakcin-a ‘vaccine’); 1b) prefixed derivatives (ca. 3%), e.g., koedukacija ‘coeducation’ ⇠ ko ‘co’ + edukacija ‘education’; 1c) neoclassical compounds (ca. 5%), both with a free first stem (e.g. euroobligacija ‘euroobligation’ ⇠ eur-as ‘euro’ + obligacija ‘obligation’) and a bound first stem (e.g. astronavigacija ‘astronavigation’ ⇠ astro ‘astro’ + navigacija ‘navigation’). Most correlative derivatives are derived from hybrid verbs adapted with the indigenous suffix -uo-ti, whereas derivatives from nouns or verbs adapted with the indigenous suffix -in-ti are rare.